Pan-Cancer Analyses Reveal Prognostic Value of Osteomimicry Across 20 Solid Cancer Types - Yang, Changsheng; Pan, Hehai; Shen, Lujun (Frontiers in Molecular Biosciences, 2020)
Background: Osteomimicry of cancer cells had been widely reported in prostate cancer and breast cancer. However, the prognostic value of osteomimicry in various cancer types remained unclear. We hypothesized that osteomimicry would result in remodeling of the tumor microenvironment and was eligible to predict patient prognosis. Methods: A comprehensive transcriptomic analysis of the osteomimicry, which was characterized by mRNA expression of SPARC, SPP1 and BGLAP, across 20 solid tumors (7564 patients) using RNA-seq data from The Cancer Genome Atlas (TCGA) was conducted. Samples of each cancer type were classified into subgroups (high vs. low) based on median value of osteomimetic markers, the associations of these markers with clinical outcomes, immune cell infiltration and immune checkpoints expression were explored. Results: Each osteomimetic marker harbored prognostic value in the pan-cancer analyses (SPARC: hazard ratio (HR)=1.10, p=0.028; SPP1: HR=1.25, p<0.001; BGLAP: HR=1.13, p=0.005). Patients with high expression of all the three genes also had significantly unfavorable survival (HR=1.61, p<0.0001) compared with those of low expression. Correlation analyses demonstrated that osteomimicry was closely related to tumor purity, dendritic cells (DC) infiltration and expression of immune checkpoints. Conclusions: Osteomimicry had prognostic value in various cancer types and the underlying mechanism might correlate to the trapping and dysfunction of DCs in the tumor microenvironment, revealing the potential of osteomimicry as a target of immunotherapy.